Status Kewarganegaraan Ganda Dan Nasib Eksil 1965: Antara Penolakan Negara Dan Pengakuan Hak Sipil - Fadila Alimah Asrarudin; Mavinda Putri; Sekar Rini Wulandari; Shafa Qolbu Dwi Putri (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
The downfall of Soekarno’s regime and the G30S PKI tragedy in 1965 led to the citizenship cancellation of Indonesian students and delegates who were previously studied abroad. Those accused of having affiliations with communism or loyalty to Soekarno had no chance to return to Indonesia and legal rights as Indonesians. This study aims to examine the political impact on the citizenship status of 1965 exiles and the challenges they faced in gaining recognition of their citizenship rights in the countries where they sought refuge. The methodology used is qualitative analysis, focusing on three countries with the highest number of exiles. Our paper indicates that most of Indonesian exiles have been revoked unilaterally by the Indonesian government, forcing them to seek alternative citizenship in the host countries. In the Netherlands, most exiles were induced to adopt Dutch citizenship due to the country’s single citizenship law, while in Russia and Czechoslovakia, where dual citizenship policies were more flexible, they found it easier to retain their Indonesian citizenship, although sometimes they faced legal limitations. In conclusion, despite experiencing injustice regarding their citizenship, these exiles continued to maintain their nationalism and hoped for recognition of their citizenship status. After the 1998 reform, the Indonesian government began to pay attention to the exiles by offering visa facilitation and reopening opportunities from them to regain their Indonesian citizenship.